Optimized microencapsulation of phenolic- and vitamin C-rich juice from Indian gooseberry by calcium-alginate ionic-crosslinking - Anne Gellie P. Pablo; Utai Klinkesorn; Sasitorn Tongchitpakdee (Journal of Agriculture and Food Research, 2025)
Indian gooseberry is a fruit renowned for its high phenolic and vitamin C content, but its strong sour and astringent taste limits its use. Therefore, developing it into a functional food ingredient would be beneficial. This study aimed to improve the fruit juice application by developing microbeads using calcium-alginate encapsulation. The encapsulation method of juice was conducted through extrusion and ionic crosslinking. The fruit juice and encapsulated juice were characterized for their total phenolic and vitamin C content. Key factors affecting encapsulation efficiency, such as juice pH, sodium alginate concentration, calcium chloride levels, and gelling time, were optimized. Results showed that adjusting the juice pH and optimizing alginate and calcium chloride concentrations significantly improved the encapsulation of phenolics and vitamin C in the microbeads. This study highlights the potential of microencapsulation in extending the usability of Indian gooseberry in functional foods and supplements. Future research can explore large-scale production and assess the stability and release properties of the microbeads in different food applications.